ANALISIS PERBANDINGAN TINGKAT EFISIENSI BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH DI INDONESIA DENGAN MENGGUNAKAN METODE STOCHASTIC FRONTIER ANALYSIS (SFA) PERIODE 2014-2016 - Vidia Tutik; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study was to examine whether the Total Deposits,Operational costs, and other Operations costs affect the Total Financing and tofind out the analysis of the efficiency level of the Sharia Commercial Banks andSharia Business Units. The type of research used is quantitative to analyze theanalysis comparing the level of efficiency of Islamic Commercial Banks andSharia Business Units in Indonesia through using the Stochastic Frontier Analysis(SFA) rule for the period 2014-2016. Based on the results of the sample criteria,there were 11 companies sampled in the study including 5 Islamic BusinessEnterprises (BUS) and 6 Sharia Business Units (UUS).The results of the study used SFA indicated "that during the period 2014-2016 BUS and UUS experienced an increase in efficiency with an averageefficiency of 0.729 for BUS and for UUS 0.7382. This shows that UUS inIndonesia is slightly better than BUS in terms of efficiency, so that UUS is moreoptimal in the level of total financing in the 2014-2016 period ". The averageefficiency of BUS and UUS ranges from 0.7 indicating that BUS and UUS inIndonesia have reached the level of efficiency even though they have not reachedfull efficiency level or 1. From the results of the panel testing hypotheses aboutthe input variables on the BUS and UUS output variables obtained results Totaldeposits have a positive and significant effect on total financing while operatingcosts and other operational costs negatively affect the significance of totalexpenditure. The assumption is made while the different test using theIndependent Sample t-test shows that there is a lack of efficiency level betweenUUS and BUS.Keywords: Efficiency, Stochastic Frontier Analysis (SFA), Islamic CommercialBank (BUS), Sharia Business Unit (UUS)